Energy efficient cluster head distribution in wireless sensor networks - Siew, Zhan Wei (2013)
The main objective of this research is to improve the cluster based wireless sensor networks lifetime by selecting appropriate cluster head (CH) via improved swarm intelligence. In general, low energy adaptive cluster hierarchy (LEACH) is one of the most common clustering protocols used to elect the cluster head. The probability model will possibly lead to a reduction in network lifetime due to the election of CH with a least desired location in the network. For network clustering, the distribution of CH selection directly influences the networks lifetime. In order to maximize the network lifetime, fuzzy logic CH selection (FLCH) and particle swarm optimisation (PSO) are embedded in LEACH protocol for better CHs distribution and hence prolong the network lifetime. PSO is lightweight heuristic optimization algorithm with each CH will move towards the best solutions by individual interaction with one another while learning from their own experience. Thus, the best selected CHs location with network global information using FLCH and PSO will be announced by the base station (BS) to the sensor nodes. Therefore it can significantly increase the networks lifetime. Evaluation and assessments have been carried out through simulation under different network topologies and it shows that FLCH selection improved first node dies (FND) round by 26.88 % as compared to LEACH. The proposed of fuzzy logic based PSO (FPSO) to automatically tuning the inertia and velocity value for each particle has further improved the FND round over the LEACH by 61.41 %. Therefore, it can be concluded that the developed FLCH and FPSO can increase the network lifetime by proper CHs selection.